Orthotopic Liver Transplantation in a Patient with Acutely Decompensated Liver Disease and Personal History of Malignant Hyperthermia. (17th September 2022) - Townsend, Elizabeth A.; Habibi, Manuchehr; Groose, Molly; McDowell, Thomas
Abstract : Introduction . Orthotopic liver transplants are characterized by sudden changes in hemodynamics, intraoperative hemorrhage, metabolic and electrolyte derangements, and arrhythmias. Many of these features are also hallmarks of malignant hyperthermia episodes and make differentiation difficult intraoperatively. Additionally, the treatment for malignant hyperthermia, dantrolene, can cause hepatotoxicity in already damaged native livers and newly reperfused organ allografts. Thus, it is imperative to avoid a triggering anesthetic in these patients. Here we report on a successful total intravenous anesthetic in a malignant hyperthermia susceptible individual undergoing an orthotopic liver transplant for acutely decompensated end-stage liver disease. Case Presentation . A 49-year-old male with a past medical history significant for malignant hyperthermia episodes as a child was admitted with decompensated alcoholic cirrhosis. He underwent uneventful total intravenous general anesthesia with propofol and sufentanil continuous infusions for an orthotopic liver transplant. He required minimal vasoactive agents to maintain a mean arterial blood pressure >65 mmHg and was extubated on postoperative day 1. Conclusions . Total intravenous anesthesia is necessary for patients with a personal history of malignant hyperthermia. However, this type of general anesthesia is difficult in the setting of fluctuating hemodynamics, hemorrhage, and changes in drug metabolism and clearance during the anhepatic and reperfusion phases of an orthotopic liver transplant. Propofol and sufentanil continuous infusions provided stable hemodynamics and an excellent plane of anesthesia throughout the case and should be considered in other individuals undergoing this procedure who require a total intravenous anesthetic.